PERFORMANCE APPRAISAL SYSTEM AND EMPLOYEE SATISFACTION - Komal Mundada; Swati (International Educational Journal of Science and Engineering, 2026)
This study examines the relationship between performance appraisal systems and employee satisfaction in modern organizations. Performance appraisal is an important human resource management practice that helps evaluate employee performance, provide feedback, and improve organizational productivity. In today’s competitive business environment, organizations are increasingly using fair and transparent appraisal systems to motivate employees and enhance job satisfaction. The study focuses on how appraisal methods, feedback mechanisms, recognition, and reward systems influence employee satisfaction and work performance. Data collected from employees and HR professionals indicates that effective performance appraisal systems improve employee motivation, productivity, and organizational commitment. However, issues such as bias, lack of transparency, and ineffective feedback still affect employee satisfaction. The study suggests adopting fair appraisal practices, continuous feedback systems, and employee development programs to improve satisfaction and organizational performance.